2012
DOI: 10.7202/1013196ar
|View full text |Cite
|
Sign up to set email alerts
|

End-users, Public Services, and Industrial Relations: The Restructuring of Social Services in Ontario

Abstract: Résumé de l'article RésuméDans la foulée de la crise financière et économique, le gouvernement de l'Ontario s'est engagé à réduire les dépenses publiques. Sur la base d'une étude détaillée, cet article illustre comment, dans ce contexte, les usagers s'imposent comme des acteurs-clés des transformations qui touchent le secteur des services d'aide et de support aux personnes souffrant d'un handicap. L'étude permet ainsi de mieux saisir le rôle important, mais complexe, joué par les usagers dans les transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…The 1980s represented the rapid integration of market forces into the provision of public services, with the NPSS sector central to this goal (Alcock, 2010;Hickey, 2012). The influence of NPM governance was clear, as non-profits were placed on a market-based footing, delivering services through top-down accountability controls and contractually-driven obligations (Carmel and Harlock, 2008).…”
Section: Austerity and Precarity In The Npss Sectormentioning
confidence: 99%
“…The 1980s represented the rapid integration of market forces into the provision of public services, with the NPSS sector central to this goal (Alcock, 2010;Hickey, 2012). The influence of NPM governance was clear, as non-profits were placed on a market-based footing, delivering services through top-down accountability controls and contractually-driven obligations (Carmel and Harlock, 2008).…”
Section: Austerity and Precarity In The Npss Sectormentioning
confidence: 99%
“…In Canada for instance, the emergence of customers as an interest group in social services in possession of individual budgets, has led to management incorporating their involvement into managerial roles, and also formerly recognising and negotiating their rights into collective agreements (Hickey, 2012). Yet, any increased influence of customer sovereignty on collective bargaining and traditional management control systems, will probably see employees and unions seeking recognition and protection of their rights.…”
Section: Managing Tensions In the Social Ordermentioning
confidence: 99%
“…Kessler and Bach (2011: 593) argue that "end users should not be considered as a homogeneous actor" and point out that not all individual end-users have the same resources and opportunities to develop effective action. Hickey (2012), for his part, showed that organizational reforms in the public sector, pursued in the context of new public management, could lead to efforts by management to co-opt and control end-users. To analyze user/patient action, we draw on Giddens' structuration theory and Bellemare and Briand's (2011) adaptation of it for the industrial relations field. Thus, in line with Giddens' hypothesis on the duality of structure, we consider that an IR system involves both the conditions for and results of the interaction of actors.…”
Section: End-users As Work Relations Actors: An Analytical Modelmentioning
confidence: 99%
“…3. While user/patient representatives can certainly express users/patients' opinions, users/patients are heterogeneous and their claims vary from one disease to another (Chalamon et al, 2013;Hickey, 2012); 4. Moreover, the researchers did not directly observe the interactions between the chosen actors (users/patients and nursing staff; user/patient representatives and union representatives).…”
Section: Conclusion Limitations and Research Avenuesmentioning
confidence: 99%